Design of a new hybrid topology of WPT system to achieve load-independent constant-current and constant-voltage output - Rehman, M. (MDPI AG, 2020)
The usage of the Wireless Power Transfer (WPT) technique for charging lithium-ion (Li-ion) batteries of electric vehicles (EVs) is increasing rapidly. The Li-ion battery requires constant current (CC) followed by constant-voltage (CV) supply for efficient battery charging and to enhance its lifespan. However, it is hard to obtain CC and CV outputs due to the variation of battery resistance during charging. Moreover, a zero-phase angle (ZPA) of the input source is essential to improve the power transfer capability. Therefore, this paper proposes a new hybrid compensation topology to achieve load-independent CC and CV behavior of the WPT system along with ZPA. Two symmetrical coils have been used in the proposed WPT system as transmitter (Tx) and receiver (Rx) coils. A comprehensive mathematical analysis for achieving CC and CV characteristics as well as for power losses is carried out. A new hybrid compensation is designed by combining Series-Series (SS) and Inductor-Capacitor-Capacitor/Series (LCC-S) compensation topologies along with two additional switches. The proposed compensation works on single resonance frequency, and it is simple, reliable, and easy to implement with only one compensation capacitor from the Rx side. Simulations are performed, and a prototype is fabricated to verify the mathematical analysis and simulation results. The overall result shows that the mathematical analysis and simulations comply with the experimental results. Full load efficiencies of 90.33 and 88.91 are achieved in the CC and CV modes, respectively. Â© 2020 by the authors.